Nurses' Experiences in the ECMO Training Process: A Qualitative Study. - Madariaga, Marcela; Moreno, Fabian; Vergel, John (Revista Cuidarte)
Introduction: In 2023, over 20,000 extracorporeal membrane oxygenation (ECMO) therapies were performed worldwide, underscoring the growing need for trained professionals in this intervention. However, standardized ECMO training programs for nurses remain limited and inconsistent. Objective: To explore professional nurses' learning experiences in ECMO therapy. Materials and Methods: A qualitative, instrumental case study design was employed with nine ECMO nurses in Colombia, using semi-structured interviews. Thematic analysis was used to identify key themes that emerged from their experiences. Results: The study revealed considerable variability in ECMO training, which included both formal and informal approaches. Participants reported gaps in theoretical knowledge and practical skills but highly valued the hands-on learning experiences provided by hospitals. Although socioemotional skills--particularly stress management in critical care settings-- were recognized as essential for building confidence, these skills were insufficiently addressed in training programs. Discussion: While the lack of standardization and the importance of clinical practice and simulation in ECMO training programs are consistent with the existing literature, teaching social-emotional competencies remains an underexplored area. Conclusions: These findings suggest the need for standardized ECMO educational programs that fully integrate technical, practical, and socio-emotional competencies and address the variability found in both formal and informal educational pathways. Reducing inconsistencies in the educational process could better equip nurses with the confidence to meet the demands of ECMO therapy, ultimately improving patient safety.